Kesenjangan Prestasi di Sekolah: Faktor-Faktor Stratifikasi yang Berperan - Windy Divaci Anastasya; Wulan Say; Dini Sri Wahyuni; Januar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this discussion is to find out the meaning of social stratification, the characteristics of social stratification, the basic causes of social stratification, the relationship between education and social stratification, and the impact of social stratification. The method used in this study is literature research. Content research uses content analysis. The results of this study are social stratification as a form of distinction or grouping of members of society vertically (stratified). There are three aspects that are characteristic of social stratification. There are differences in abilities including differences in lifestyle, differences in rights and access in utilizing resources. The basis for the formation of social layers is as follows wealth. power and authority, honor, knowledge, and descent, the relationship between social stratification and learning achievement is very close, there are positive and negative impacts of social stratification.